The Turkish Adaptation of Athletic Coping Skills Inventory-28 (ACSI-28): The validity and reliability study - Volkan Ozcan; Mehmet Gunay (Selcuk University, 2017)
It is the aim of this study is to test the validity and reliability of the Turkish version of Athletic Coping Skills Inventory-28 (ACSI-28) developed by Smith et al. (28). Back-translation technique was employed during the process of Turkish translation of ACSI-28. The scale is 28 items instrument which have seven subscales, namely coping with adversity, concentration, coachability, confidence and achievement motivation, goal setting/mental preparation, peaking under pressure, and freedom from worry. Respondents of the ACSI-28 indicate the extent to which they agree with each statement on a four-point Likert scale, ranging from 0 (Almost never) to 3 (Almost always). Items number 9 and 12 have been removed from the scale, which are not meaningful t value according to the analyze. With the remaining 26 items, the analyzes were repeated. After review, all the items were maintain in place. In order to test the inventory's reliability, its Cronbach's Alpha scores was calculated and found for each subscales coping with adversity .66, concentration .68, coachability .71, confidence and achievement motivation .65, goal setting/mental preparation .70, peaking under pressure .80, and freedom from worry .62. The scale is shown to be valid and reliable.